Market intelligence for rice, sorghum and yam in Benin and Ghana: Key findings from 2024 surveys - Adinsi, L.; Agey-Holmes, A.; Akissoe, N.; Amma Asante-Poku, N.; Anihouvi, E.; Bouniol, A.; Dufour, D.; Honfozo, L.; Hotegni, F.; Maki Sy, M.; Mbeguie, D.; Mendez del Villar, P.; et al. (2024)
Rice, sorghum and yam all play a crucial role in food security across West Africa, being consumed in various forms at every meal, both in rural and urban areas. Value chains and markets of these three major crops are constantly evolving due to societal and environmental factors such as growing urban populations, changing consumer preferences and changes in suitable agricultural areas in relation with the climate crisis. In order to support breeding programs in anticipating emerging requirements in terms of crop agricultural performance, processing ability and end-product quality, the CGIAR Initiative on Market Intelligence and Product Profiles (MIPPI) develop survey methods adapted for the collection and analysis of market information and users’ preferences data. In this poster, we summarize the key findings of a regional study of rice, sorghum and yam value chains in Benin and Ghana and provide an informational basis on market trends and key preferred quality traits to support breeding activities and varietal adoption